Using CEFR Can Do Statements to Enhance Students' Self-Regulated Learning in Outcome-Based Education - Moh. Fauzi Bafadal; Humaira; Muhammad Hudri (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
Self-Regulated Learning (SRL) is essential for the successful implementation of Outcome-Based Education (OBE) because students are expected to actively monitor, evaluate, and regulate their own learning processes. However, previous studies have largely focused on the accuracy of self-assessment rather than its role in supporting learning regulation. This study investigated the effectiveness of CEFR Can Do Statements as a self-assessment strategy for enhancing students’ SRL. An explanatory sequential mixed-methods design was employed involving 60 Pharmacy and Midwifery students enrolled in English for Specific Purposes courses at Universitas Muhammadiyah Mataram. Quantitative data were collected through a Self-Regulated Learning questionnaire and analyzed using paired-sample and independent-sample t-tests, while qualitative data were obtained through classroom observations, interviews, and Focus Group Discussions. The findings revealed a statistically significant improvement in students’ Self-Regulated Learning, with the experimental group outperforming the control group (p < .001). The intervention produced a large practical effect (Cohen’s d = 1.47). Qualitative findings indicated that self-monitoring, goal setting, reflective learning, and learning autonomy emerged as the most prominent themes, demonstrating meaningful changes in students’ learning behaviors. This study extends the role of CEFR Can Do Statements beyond language assessment by demonstrating their function as metacognitive tools that support learning regulation within an OBE framework. The findings suggest that CEFR-based self-assessment can serve as an effective strategy for promoting learner autonomy and strengthening the implementation of Outcome-Based Education in higher education.